A New Vlc System for Localization in Underground Mining Tunnels - Soto-Gomez, J; Seguel-Gonzalez, F (IEEE Computer Society, 2017)
In this paper we present a new system that uses new technology that has the ability to transmit data using light emitting diodes (LED) and a photodetector (PD) capable of sensing very soft changes of light. The system developed in conjunction with the trilateration technique can be used for localizing personnel as well as machinery in underground mining tunnels. Simulations are performed, and comparisons are made with other well-known techniques in terms of the location estimation error. Overall, it is shown that the proposed system is a viable option for localization in underground mining tunnels. © 2003-2012 IEEE.
Keywords: Visible light communications; localization; trilateration